A resposta policial restaurativa no campo da administração da justiça e dos conflitos no Brasil : a experiência do Programa Mediar RS da Polícia Civil do Rio Grande Do Sul - Leão, Aline Mariano (2020)
This research proposes to investigate restorative police response in brazilian civil police, considering the background from which it emerges, and how it is carried out in practice, based on the experience of Rio Grande do Sul State Civil Police Program, Mediar RS. The elected perspective was Administration of Justice as field of sociology, in particular, studies of state conflict management in brazilian criminal justice. The restorative police response is presented as an institutional and state microsystem, based on a qualitative approach, data construction by interviews with system actors, and participant observation in two Mediation Police Offices at Rio Grande do Sul. The speech analysis of civil police mediators seeks to interpreting how these operators legitimize and sustaining their action at legal and judicial fields of disputes. It was identified that the police restorative response was an institucional effort to regain power and legitimacy in administration justice field, increasing disputes under a logic guided by operational efficiency, and containing of conflictual escalation and police records. It was also found that obstacles and criticisms to this model are related to the idea of what real police work would be, a permanent problematic inside and outside the institutional and state scope. In addition, it was found that, for the civil police mediators, this work resignifies whats is be a police agent, and what a police agent do, based on the perception of a positive and satisfactory resolution response, focusing on the will of people, in opposition to persecutory and punitive traditional focus.